Factors influencing zakat compliance behavior on saving - Noor Azman, Farah Mastura; Bidin, Zainol (Maryland Institute of Research (MIR), 2015)
In most of the states in Malaysia, the collection of zakat on saving is reported as third largest collection after zakat on employment income and zakat on business.However, the collection of zakat including the zakat on saving is still unsatisfactory.Previous empirical evidences reported that many factors that influence individual in paying zakat.Thus, this study aims at to determine the variables that influence the individual in paying zakat on saving i.e. the relationship between the variables of attitude, the referent group, religiosity and perceived corporate credibility with zakat compliance behavior on saving.Data was analyzed by applying multiple regression analysis.The data was collected from 80 individual Muslim employees who are working at Universiti Utara Malaysia.The results of the study indicated that all the variables significantly influence zakat compliance behavior on saving.Based on the results, it can be concluded that zakat compliance behavior on saving could be predicted by his or her attitude, the referent group, religiosity and perceived corporate credibility at 34% level.In view of the results, some implication and recommendation were also discussed.